The impact of motivation factors and intention to adopt Jordan as a destination for medical tourism in the Middle East - Ahmad Al Adwan (Innovative Marketing)
The study aimed to investigate the impact of motivation factors on an individual’s decision to choose Jordan as their primary tourism destination in the Middle East. The decision to choose Jordan as a medical destination will be analyzed based on factors, including government support; push engagement, and image perception. To this end, the study will gather data from 300 online individuals who have traveled to the Middle East for medical purposes. A qualitative approach will be adopted to provide insight into an individual’s preference for Jordan as the primary medical destination. A Partial Least Squares Structural Equation Modeling method was adopted, which allows for the creation of relations with different variables. The study’s findings indicate that people from rural areas in the Middle East preferred Jordan as a medical destination. Also, more women than men traveled to Jordan for medical purposes. Finally, more single people than married persons choose medical assistance in Jordan. Future studies are needed to ascertain how factors such as quality and cost influenced medical tourism into Jordan. AcknowledgmentsI would like to thank the Business School at Al Ahliyya Amman University, Jordan. Specifically, many thanks go to the departments of marketing.